(untitled) (Journal of the College of Education for Women, 2023)
The present paper aims at investigating the linguistic image portrayed by UNICEF reports on the Iraqi child from a critical discourse analysis perspective during Covid19 pandemic (2020). The paper attempts to fill a gap in research literature concerning the linguistic construction of the Iraqi child by the UNICEF reports during the critical health crisis of Covid19. Van Leeuwen’s (2008) approach of social actor representation has been adopted for this purpose. From Van Leeuwen’s approach, the category of determination (single determination and overdetermination) has been selected to be the main analytical tool for its high compatibility with the set of objectives put forward to figure out how such a globally effective and easily accessible discourse constructs the Iraqi child. The research is qualitative in nature and the findings are supported by some figures and percentages. The paper has come up with a number of conclusions that spot an interesting situation. First, The USRs do not imprison the IC within a limited vision that usually accompanies the linguistic reliance towards single determination. Second, the USRs have assigned the IC a number of social roles that are compatible with the IC him/herself. This leads to the third conclusion which states that the USRs put the IC in wider perspectives that come within the domains of reality which is bound to the surrounding physical environment. Fourth, although the social roles assigned to the IC vary in the attitude they embed towards the IC, the neutral roles have outperformed the positive and negative ones.